Evaluating Cognitive Enrichment for Zoo-Housed Gorillas Using Facial Recognition - Brookes, Otto; Gray, Stuart; Bennett, Peter; Burgess, Katy V.; Clark, Fay E.; Roberts, Elisabeth; Burghardt, Tilo (Frontiers in Veterinary Science, 2022)
The use of computer technology within zoos is becoming increasingly popular to help achieve high animal welfare standards. However, despite its various positive applications to wildlife in recent years, there has been little uptake of machine learning in zoo animal care. In this paper, we describe how a facial recognition system, developed using machine learning, was embedded within a cognitive enrichment device (a vertical, modular finger maze) for a troop of seven Western lowland gorillas (Gorilla gorilla gorilla) at Bristol Zoo Gardens, UK. We explored whether machine learning could automatically identify individual gorillas through facial recognition, and automate the collection of device-use data including the order, frequency and duration of use by the troop. Concurrent traditional video recording and behavioural coding by eye was undertaken for comparison. The facial recognition system was very effective at identifying individual gorillas (97% mean average precision) and could automate specific downstream tasks (for example, duration of engagement). However, its development was a heavy investment, requiring specialised hardware and interdisciplinary expertise. Therefore, we suggest a system like this is only appropriate for long-term projects. Additionally, researcher input was still required to visually identify which maze modules were being used by gorillas and how. This highlights the need for additional technology, such as infrared sensors, to fully automate cognitive enrichment evaluation. To end, we describe a future system that combines machine learning and sensor technology which could automate the collection of data in real-time for use by researchers and animal care staff.